2017
DOI: 10.1371/journal.pone.0174321
|View full text |Cite
|
Sign up to set email alerts
|

C-type allatostatins mimic stress-related effects of alarm pheromone on honey bee learning and memory recall

Abstract: As honey bee populations worldwide are declining there is an urgent need for a deeper understanding of stress reactivity in these important insects. Our data indicate that stress responses in bees (Apis mellifera L.) may be mediated by neuropeptides identified, on the basis of sequence similarities, as allatostatins (ASTA, ASTC and ASTCC). Effects of allatostatin injection are compared with stress-related changes in learning performance induced by the honeybee alarm pheromone, isopentylacetate (IPA). We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Exposure to both the sting alarm pheromone and to IAA alone impairs appetitive olfactory PER conditioning in a dose-dependent manner, but leaves sucrose responsiveness intact 35 . Learning impairment is mediated probably by allatostatins, in particular by the C-type allatostatin (ASTCC), which might be therefore responsible for the stress-induced analgesia 44 . If and how allatostatins interact with aminergic pathways to modulate learning and memory remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to both the sting alarm pheromone and to IAA alone impairs appetitive olfactory PER conditioning in a dose-dependent manner, but leaves sucrose responsiveness intact 35 . Learning impairment is mediated probably by allatostatins, in particular by the C-type allatostatin (ASTCC), which might be therefore responsible for the stress-induced analgesia 44 . If and how allatostatins interact with aminergic pathways to modulate learning and memory remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridisation shows that Spot/vp-like mRNA, similar to mollusk op/ct, is distributed in various kinds of neurons in cerebral ganglion, such as 6th and 7th neuronal clusters involved in reproductive regulation, and 8th and 9th in olfaction, learning and memory regulation [45][46][47]. Spot/vpr-like mRNA is expressed in F-cells of hepatopancreas, the main sites of enzyme synthesis, suggesting that the system may participate in the regulation of hepatopancreas on digestion, metabolism and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…A notable exception is in the Diptera, including both Drosophila melanogaster ( Kreienkamp et al 2002 ) and the mosquito Aedes aegypti ( Mayoral et al 2010 ), where two AST-C receptors have been identified ( Kreienkamp et al 2002 ; Mayoral et al 2010 ). Nonetheless, in those insects in which the functional effects of multiple AST-Cs have been examined ( Audsley et al 2013 ; Dong et al 2017 ; Urlacher et al 2016 , 2017 ), it has been suggested that the peptides act on the single receptor that was identified, although potentially with different affinities (e.g., Urlacher et al 2016 ). Interestingly, in one of the few crustaceans in which neuropeptide receptors have been predicted, H. americanus , three different AST-C receptors were recently identified using a transcriptome derived from mixed nervous system tissues ( Christie et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%